Enantiogroup‐Differentiating Biocatalytic Reductions of Prochiral Cs‐Symmetrical Dicarbonyl Compounds to meso Compounds. Issue 24 (27th April 2015) - Skoupi, Marc; Vaxelaire, Carine; Strohmann, Carsten; Christmann, Mathias; Niemeyer, Christof M.
Abstract The stereoselective reduction of symmetrical prochiral dicarbonyl compounds bearing enantiotopic carbonyl groups yields several stereogenic centers in one step. In a proof‐of‐concept study, a new approach is described for the enzymatic desymmetrization of 5‐nitrononane‐2, 8‐dione via sequential biocatalytic reduction steps utilizing ketoreductases to yield all possible diastereomers of 5‐nitrononane‐2, 8‐diol.